Invitation withdrawn: humanitarian action, United Nations peacekeeping, and state sovereignty in Chad. (22nd July 2013) - Karlsrud, John; Felix da Costa, Diana
Abstract : This paper looks at the three‐way relationship between the Government of Chad, humanitarians, and the United Nations Mission in the Central African Republic and Chad (MINURCAT) from 2004 until June 2011. Chad was never comfortable with the international presence of either humanitarians or peacekeepers and asserted its sovereignty increasingly during this period. MINURCAT was deployed in 2008 to protect humanitarian workers and to facilitate the provision of humanitarian assistance in eastern Chad. This association between the UN mission and humanitarian agencies contributed to making the latter the target of repressive practices by the government, such as the imposition of armed escorts. Facing a steep learning curve, Chad and its state officials gradually appropriated the discourse of the humanitarian and international community and ultimately, in 2010, requested the departure of MINURCAT, claiming that they could meet the protection needs of vulnerable populations in eastern Chad on their own.